REVITALISASI SEJARAH KERINCI MELALUI PEMBELAJARAN INTERAKTIF UNTUK PENGUATAN PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL - Nandia Pitri; Minal Elpia Trisko (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
The integration of local history into educational practices is vital for fostering students' character development and preserving cultural heritage. This study explores the revitalization of Kerinci’s history through interactive learning as a strategy to strengthen character education based on local wisdom. Utilizing a qualitative approach with a case study method, the research was conducted in schools in Kerinci Regency. Data collection methods included in-depth interviews, classroom observations, and document analysis involving history teachers, students, and school administrators. The findings indicate that integrating Kerinci’s historical narratives and traditions into interactive learning methods, such as storytelling, role-playing, and project-based activities, significantly enhances students’ engagement and understanding. These approaches not only make learning more enjoyable but also effectively instill values such as nationalism, respect, and cultural pride. Furthermore, challenges identified in implementing these methods include limited resources and teachers’ unfamiliarity with interactive techniques. This study concludes that revitalizing Kerinci’s history through interactive learning is a meaningful way to connect education with local culture and to cultivate strong character foundations in students. Recommendations include developing localized curriculum materials, conducting teacher training on interactive methodologies, and increasing institutional support for integrating local history into education.